Impact of gaps in care for malnourished patients on length of stay and hospital readmission - Joanna Bryan Ringel; Deanna Jannat-Khah; Rachel Chambers; Emily Russo; Louise Merriman; Renuka Gupta (BMC, 2019)
Abstract Background Few published articles have focused on identifying the gaps in care that follow a malnutrition diagnosis and their effects on length of stay (LOS) and 90-day readmission. We hypothesized that length of stay and readmission were associated with these gaps in care. Methods Two registered dietitians retrospectively reviewed charts of 229 adult malnourished patients admitted to a medicine unit to determine their system level gap in care: communication, test delay, or discharge planning. In this secondary analysis, both readmission and length of stay were regressed on each gap in care. Results Any system level gap was associated with a greater length of stay (β: 1.48, 95% CI: 1.15-1.91) and specifically the gap related to procedure/testing (β: 2.01, 95% CI: 1.62-2.47) resulted in a two-fold increase in length of stay. There was no association between 90-day readmission and any of the gaps in care. Conclusions There was a strong association between those who had any gap in their care and increased length of stay. Mitigating gaps in care may decrease length of stay and, in turn, result in less risk of infection and could potentially lead to reduced healthcare costs.